2019
DOI: 10.18203/2349-2902.isj20190554
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of aetiology of acute intestinal obstruction

Abstract: Background: Acute intestinal obstruction is one of common abdominal emergency and is associated with significant morbidity and mortality especially if it progresses to bowel ischemia. The diagnosis and management of the patient with intestinal obstruction is one of the more challenging emergencies that a general surgeon can come across. Although the mortality due to acute intestinal obstruction is decreasing with better understanding of pathophysiology and improvement in diagnostic techniques, fluid and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The mortality has been decreasing consistently, associated medical problems (like respiratory cardiac or metabolic diseases) and advanced age carries a considerable contribution in adding the mortality. 12,13 In our study the incidence of intestinal obstruction in males was 42 and that of females was 18. Male to female ratio is 2:1.…”
Section: Discussionsupporting
confidence: 44%
“…The mortality has been decreasing consistently, associated medical problems (like respiratory cardiac or metabolic diseases) and advanced age carries a considerable contribution in adding the mortality. 12,13 In our study the incidence of intestinal obstruction in males was 42 and that of females was 18. Male to female ratio is 2:1.…”
Section: Discussionsupporting
confidence: 44%
“…Another study also designated abdominal pain as the most common symptom followed by vomiting as the second most prevalent symptom, similar to our study. 5 Tiwari et al in their study, however, found the peak incidence of distension in the abdomen as the most recurrent symptom closely followed by constipation and vomiting. 13 About the site of obstruction, the small intestine was more common than that of the large intestine.…”
Section: Discussionmentioning
confidence: 83%
“…Nasiruddin et al also reported peak incidence of IO among males with a prevalent % of 66. 5 Tiwari et al also recorded that IO was found to occur predominantly in males (65%) compared to females (35%). 13 Abdominal pain turned out to be the most common symptom of IO in our patients, with the occurrence of 91.7% followed by vomiting (18.3%), distension, constipation and tenderness in sequential order.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations